An assessment of selected public elementary school libraries in Quezon City - Manalo, Janice V. (2002)
An assessment of selected public school libraries in Quezon City was conducted to present the current situation of library facilities and equipment in such institutions. Professional teachers is not enough, it is also through acceptable school library facilities and equipment can the government's vision of quality education for the masses be totally met. It is with this reason that this study was pursued.